The factors affecting deep vein thrombosis following laparoscopic hysterectomy and the factors affecting it - Hasan Mohammadipour Anvari; Mina Zeinalzadeh; Nafiseh Sheghaghi Ilkhchi; Dara Alvandfar (Mashhad University of Medical Sciences, 2021)
Introduction: Due to the acceptance of laparoscopic hysterectomy by surgeons and patients and the fact that the prevalence of some complications of hysterectomy such as deep vein thrombosis, which is a dangerous and unpredictable complication, has not been accurately determined; this study was performed with aim to determine the factors affecting deep vein thrombosis following laparoscopic hysterectomy.Methods: This descriptive cross-sectional study was performed in 2020 with participation of 55 women candidates for laparoscopic hysterectomy in Alzahra Hospital, Tabriz. The prevalence of deep vein thrombosis and its effective factors was evaluated with D-dimer test and the researcher-made checklist (extracted from articles). Data were analyzed by SPSS software (version 22) and Spearman coefficient test. P<0.05 was considered statistically significant.Results: The prevalence of deep vein thrombosis in the present study was 12.72%. Variables of age>60 years (P=0.001), high body mass index (P=0.009), previous history of deep vein thrombosis (P=0.008), history of long-term use of contraceptives (P=0.005) and prolonged immobility in the recent three months (P=0.011) were directly related to the incidence of deep vein thrombosis after abdominal hysterectomy.Conclusion: The prevalence of deep vein thrombosis after laparoscopic hysterectomy in the present study was 12% that old age, high body mass index, use of contraceptives pills and complete immobility are its risk factors. It is recommended that preventive and therapeutic measures be considered before surgery for patients at risk for this complication.